Evaluation of Pellet Binders on Pellet Durability Index of a High-Fat Swine Diet - H. K. Wecker; C. E. Evans; A. Yoder; M. Saensukjaroenphon; C. R. Stark; K. A. Barry; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2018)
The objective of this study was to evaluate the addition of different pellet binders on pellet quality of a grower swine diet by measuring pellet durability index (PDI). Dietary treatments consisted of a corn-soybean meal-based control diet with 20% dried distillers grains with solubles and 4% choice white grease, the control diet with 0.6% lignosulfonate (AMERI-BOND 2X; LignoTech USA Inc.; Rothschild, WI), or the control diet with increasing levels of a pasta by-product (2.5, 5.0, or 10.0%; International Ingredients, St. Louis, MO). Pellet binders were added to the control diet in the place of corn to create dietary treatments. Each treatment was pelleted in 333 lb batches at 3 separate periods to provide 3 replications per treatment. Pelleting run was considered the experimental unit and time of processing served as the blocking factor. Order of pelleting dietary treatments was randomized within each time period. Corn was ground to approximately 600 μm. Diets were pelleted via steam conditioning (10- × 55-in. Wenger twin staff conditioner, Model 150) and using a 30-horsepower pellet mill (1012-2 HD Master Model, California Pellet Mill) with a 5/32- × 1-in. pellet die. During each processing run, pellet samples were collected throughout the run and immediately placed in an experimental counter-flow cooler for 10 minutes. After cooling, samples were analyzed for pellet durability index using the Holmen NHP 100 (TekPro Ltd, Norfolk, UK) for 30 seconds. There was no evidence (P>0.172) of difference for the effect of treatment on conditioner temperature, hot pellet temperature, or production rate. The average conditioner temperature, hot pellet temperature, and production rate were 185.9°F, 188.2°F, and 1,364 lb/h, respectively. The diet containing lignosulfate improved (P<0.001) PDI compared to the control diet. Increasing pasta by-product from 2.5 to 10% increased the PDI (P<0.01) compared with the control diet. Diets containing 2.5% pasta by-product had lower PDI compared to those with lignosulfonate, diets with 5% pasta by-product and lignosulfonate had similar PDI, and diets containing 10% pasta by-product had increased PDI compared to the lignosulfonate treatment. In conclusion, adding pellet binders to the high fat finisher diets improved PDI by 7.4 to 10.7%. Adding 5% pasta by-product improved PDI similar to that of lignosulfonate and adding 10% pasta by-product further improved PDI compared to lignosulfonate.
Keywords: Pellet durability index; pellet binder; pellet quality